A substrate binding model for the KEOPS tRNA modifying complex - Jonah Beenstock (Nature Portfolio, 2020)
KEOPS is an evolutionary conserved complex with a core of four core subunits—Pcc1, Kae1, Bud32 and Cgi121—that catalyzes the universal and essential tRNA modification N6-threonylcarbamoyl adenosine (t6A). Here the authors describe a Cgi121-tRNA crystal structure and new composite model of the KEOPS holo-enzyme-substrate complex that shed light on the t6A catalytic cycle and its regulation.